Association of nationality and education with oral health: a screening programme in Northern Italy. (13th November 2019) - Del Pin, M; Varadi, G; Pascut, S; Tito, R; Dovier, A; Covre, C; Honsell, F; Valent, F; Parpinel, M; Brusaferro, S
Abstract: Background: Socioeconomic status (SES) has been proposed as an important determinant of oral health outcomes. The aim of this project is to assess the association between nationality, parents' educational level and oral health in a sample of children in Udine, Italy. Methods: Between February and May 2018, in the context of a screening programme carried out to evaluate the oral health status in 6-year-old children, parents filled out a questionnaire investigating behavioural, socioeconomic and demographical factors. For each child the number of decayed, missing and filled deciduous teeth (dmft) and caries prevalence (CP) were assessed. Results: The screening was conducted on 976 children, 705 (72%) Italian (I) and 271 (28%) foreign residents (F). Not-Italian nationality significantly increased the CP (F: 59.32%; I: 32.74%; RR: 1.81 [95% CI: 1.57-2.10]; Risk Difference: 26.59 [95% CI: 19.98-33.19]) and dmft median value (F: 2±5; I:0±1; p < 0.0001). Stratified by level of education, the differences between I and F were significant when both parents had low educational level (CP: RR = 1.62 [95%; CI: 1.00-2.62]; dmft: F = 5±5; I = 0±3; p < 0.05) and when both parents had high school education (CP: RR = 1.45 [95%; CI: 1.14-1.84]; dmft: F = 2±6; I = 0±2; p < 0.001). Otherwise, when both parents had university degree, nationality did not increase significantly the outcome (CP: RR = 1.17 [95%; CI: 0.91-1.50; p > 0.1]; dmft: F = 0±2; I = 0±0; p > 0.1). Conclusions: The analyses suggest that being a foreign resident is a risk factor for lower child oral health. Moreover, parents' educational level seems to be an effect modifier: when parents had a university degree there was no significant difference between Italians and foreign residents, otherwise the lower the level of education, the greater the difference between the categories. These data may help to identify particularly vulnerable groups and to develop preventive strategies. Key messages: These findings confirmed the presence of a vulnerable population (foreign residents) in which socioeconomic factors had stronger associations to oral health than Italian citizens. Further research may be useful to identify both protective and risk factors associated with different nationality, in order to evaluate specific interventions in low-SES groups.